Nowy ład, nowy chaos. Refleksje o mieście i transformacji na marginesie książki Chaos Warszawa Porządki przestrzenne polskiego kapitalizmu - Szmidt, Olga (Śląskie Studia Polonistyczne, 2019)
The article critically analyses the book Chaos Warszawa. Porządki przestrzenne polskiego kapitalizmu [Warsaw-Chaos. Spatial Orders of Polish Capitalism] by Joanna Kusiak. An attempt at juxtaposing the said publication with other takes on today’s Warsaw space, the city’s post-World War II rebuilding, and post-1989 transformation, results in complex yet reappearing image of Warsaw as a city tainted with chaos. Considering different ways out of this stalemate, on the other hand, as in approaching the problem from another angle, is the aim of the present text. The book by Kusiak is a starting point for a discussion regarding not only space and chaos, but also theoretical discourse related to the city space and its meaning for Warsaw’s development.